Analyzing the Chinese budgetary responses to COVID-19: balancing prevention and control with socioeconomic recovery. Issue 5 (27th October 2020) - Wu, Shaolong; Lin, Muhua
Abstract : Purpose: The purpose of this study is to analyze the scope and magnitude of Chinese budgetary responses to the coronavirus disease 2019 (COVID-19) pandemic. Design/methodology/approach: This study analyzes budgetary response in China by means of public reports, news reports and policy documents. Findings: The Chinese responses were comprehensive, flexible and fast. Through the normal authorization process, simplifying procedures of budget allocation and special legislative approval after the surge of COVID-19 cases, China used many budgetary measures to help suffering businesses and households to buffer the economic difficulties caused by the pandemic. It also increased public health spending very quickly so subnational governments could control and prevent the pandemic with the necessary resources. International relief efforts have also been increased. These findings show the unique strength of the Chinese political system, which is very flexible and quick in resource mobilization. Originality/value: This study offers a quick review of the Chinese budgetary responses to the COVID-19 pandemic. It also highlights some of the future concerns and needs of the Chinese government in domestic and global health areas.